Anti-malarial activity of methanol extracts of Anacardium Occidentale linn. (Anacardiaceae) and Psidium Guajava Linn. (Myrtaceae) leaves (2023)
The antiplasmodial activities of Anacardium occidentale L. and Psidium guajava L. have been severally reported in literature. β--hematin production is an exclusive method implemented by Plasmodium protozoan parasite to produce very high quantities of redox active free hemoglobin. The purpose of this study is to determine the effectiveness of methanol extracts of Anacardium occidentale L. and Psidium guajava L. leaves used to treat severe malaria attacks in Nigeria and their impact on the inhibition of β-hematin production. The LD50 values for the leaves of Psidium guajava L. and Anacardium occidentale L. in methanol extracts were >5000 mg/kg and 1600 mg/kg, respectively. On Day 4, Plasmodium berghei-infected mice (NK 65) displayed comparable chemo-suppression of parasitaemia for A. occidentale (73.88%) and P. guajava (72.75%). However, both extracts had lower activities than chloroquine (83.58 %; 20 mg/mL). A. occidentale had a higher inhibition of formation of β hematin, with IC50 of 36.1 ± 0.52 µg/mL than P. guajava with IC50 of l0.25 ± 0.07 µg/mL and chloroquine with IC50 of 2.71±0.39 µg/mL. According to the current study, methanol extracts of the leaves of Anacardium occidentale L. and Psidium guajava L. have similar antimalarial effects and are associated with a reduction in β-hematin production. The in vivo antimalarial activity of Psidium guajava L. and Anacardium occidentale L. were equivalent, but Psidium guajava L. possessed a more potent inhibitor of the production of β-hematin.